1996
DOI: 10.1038/380227a0
|View full text |Cite
|
Sign up to set email alerts
|

Infrared emission spectra of candidate interstellar aromatic molecules

Abstract: Interstellar dust is responsible, through surface reactions, for the creation of molecular hydrogen, the main component of the interstellar clouds in which new stars form. Intermediate between small, gas-phase molecules and dust are the polycyclic aromatic hydrocarbons (PAHs). Such molecules could account for 2-30% of the carbon in the Galaxy, and may provide nucleation sites for the formation of carbonaceous dust. Although PAHs have been proposed as the sources of the unidentified infrared emission bands that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 21 publications
4
116
1
Order By: Relevance
“…This disfavors assignment to hot bands, because as the radiation Ðeld and average photon energy decrease, so should hot band and overtone emissions. Finally, our data for PAHs as large as coronene show no evidence for hot bands or overtone emission for any vibrational mode between 2È16 km (Cook et al 1996). While it cannot be ruled out that combination bands and overtones are responsible for some of the minor features of methylated/hydrogenated PAHs, it seems that these processes are not important for normal PAHs.…”
Section: Hot-band and Overtone Emissionscontrasting
confidence: 59%
See 1 more Smart Citation
“…This disfavors assignment to hot bands, because as the radiation Ðeld and average photon energy decrease, so should hot band and overtone emissions. Finally, our data for PAHs as large as coronene show no evidence for hot bands or overtone emission for any vibrational mode between 2È16 km (Cook et al 1996). While it cannot be ruled out that combination bands and overtones are responsible for some of the minor features of methylated/hydrogenated PAHs, it seems that these processes are not important for normal PAHs.…”
Section: Hot-band and Overtone Emissionscontrasting
confidence: 59%
“…However, because Gomez all aromatic molecules exhibit this feature, it is not a deÐni-tive diagnostic for assignment of the UIRs to a particular carrier. The extension of gas-phase emission studies deeper into the IR made possible by our development of the SPIRES technique (Schlemmer et al 1994 ;Cook et al 1996), has shown that neutral PAHs as large as coronene fail to reproduce the IR emissions in both band positions and relative intensities (Cook et al 1998). …”
Section: Introductionmentioning
confidence: 99%
“…7 Similarly, C 2 H is a key radical in the formation of polycyclic aromatic hydrocarbons (PAHs), 6 which are believed to play an important role in interstellar chemistry. 8,9 Benzene (C 6 H 6 ), the simplest aromatic hydrocarbon, is considered to be a precursor for larger PAH formation and its recent identification on Titan 10 strongly suggests that much more complex PAH synthesis may proceed in the cold atmosphere of the Saturnian moon. Recently, Mebel and coworkers 11 proposed a novel Ethynyl Addition Mechanism (EAM) as a viable alternative to the high-temperature Hydrogen-Abstraction-C 2 H 2 -Addition (HACA) 12 mechanism for the formation of PAHs at very low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The evaporated PAHs, however, form a sample in thermal equilibrium, while UV-excited PAHs combine low rotational excitation with high vibrational excitation, a situation that more closely resembles the assumed conditions in the ISM. Perhaps the most sophisticated emission spectroscopy experiments have been reported by the group of Saykally, who used a cryogenically cooled grating spectrometer to greatly suppress the blackbody background radiation, in combination with an extremely sensitive IR detector (Cook et al , 1996. Thus, emission spectra of UV excited PAHs were recorded over the entire IR range from 3 to 15 µm.…”
Section: Infrared Emission Spectramentioning
confidence: 99%
“…One of the main conclusions of the emission spectra of Cook et al (1996) was that neutral PAH species would not be able to explain the UIR emission features and the presence of a substantial fraction of ionized PAHs was invoked. In fact, already early on in the history of the PAH hypothesis it was realized that ionized PAHs may play an important role because of the low ionization potentials of PAHs combined with the UV pump fields that are necessary to induce IR emission (Allamandola et al 1989).…”
Section: Ir Spectroscopy Of Ionic Pah Speciesmentioning
confidence: 99%